Postoperative Adjuvant Therapy Versus Surgery Alone for Stage IIB–III Esophageal Squamous Cell Carcinoma: A Phase III Randomized Controlled Trial. (19th August 2021) - Ni, Wenjie; Yu, Shufei; Xiao, Zefen; Zhou, Zongmei; Chen, Dongfu; Feng, Qinfu; Liang, Jun; Lv, Jima; Gao, Shugeng; Mao, Yousheng; Xue, Qi; Sun, Kelin; et al.
Abstract : Background: Retrospective studies have shown that adjuvant treatment improves survival of patients with stage IIB–III esophageal squamous cell carcinoma, but there is no evidence from prospective trials so far. Materials and Methods: Patients with pathological stage IIB–III esophageal squamous cell carcinoma were randomly assigned to receive surgery alone (SA), postoperative radiotherapy (PORT), or postoperative concurrent chemoradiotherapy (POCRT). PORT patients received 54 Gy in 27 fractions; the POCRT group received 50.4 Gy in 28 fractions, plus concurrent chemotherapy with paclitaxel (135–150 mg/m 2 ) and cisplatin or nedaplatin (50–75 mg/m 2 ) every 28 days. The primary endpoint was disease-free survival (DFS), and the secondary endpoint was overall survival (OS). Results: A total of 172 patients were enrolled (SA, n = 54; PORT, n = 54; POCRT, n = 64). The 3-year DFS was significantly better in PORT/POCRT patients than in SA patients (53.8% vs. 36.7%; p = .020); the 3-year OS was also better in PORT/POCRT patients (63.9% vs. 48.0%; p = .025). The 3-year DFS for SA, PORT, and POCRT patients were 36.7%, 50.0%, 57.3%, respectively ( p = .048). The 3-year OS for SA, PORT, and POCRT patients were 48.0%, 60.8%, 66.5%, respectively ( p = .048). Conclusion: PORT/POCRT (especially POCRT) may significantly improve DFS and OS in stage IIB–III esophageal squamous cell carcinoma. Implications for Practice: The results of this phase III study indicated that postoperative radiotherapy/postoperative concurrent chemoradiotherapy (PORT/POCRT) could significantly improve disease-free survival and overall survival in stage IIB–III esophageal squamous cell carcinoma compared with surgery alone with acceptable toxicities. In-field and out-of-field recurrences were comparable between the POCRT and PORT groups, which demonstrates the rationality and safety of the radiation field used in this study. The postoperative regimens in this trial might be accepted as standard treatment options for pathological stage IIB–III esophageal cancer. Larger sample size prospective randomized trials to identify the value are warranted. Abstract : Esophageal cancer is the eighth most common cancer and the sixth most common cause of cancer death worldwide. This article focuses on best treatment options for patients with esophageal squamous cell carcinoma.